2010
DOI: 10.1177/1082013209353221
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Ultra Low Oxygen Effects and Involvement of Ethylene in Chilling Injury of ‘Rojo Brillante’ Persimmon Fruit

Abstract: The effects of storage temperature, inhibition of ethylene action by treatment with 1-methylcyclopropene (1-MCP) and ultra low oxygen (ULO) atmosphere on chilling injury (CI), fruit firmness and ethylene production in the astringent 'Rojo Brillante' persimmon fruit were investigated. CI symptoms were manifested as a very dramatic loss of firmness after fruit transfer from cold storage to shelf-life conditions (18 °C). During cold storage, fruit softening appeared more rapidly in fruit stored at the intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The main CI symptom of this cultivar is a fast firmness loss. This flesh softening can be exhibited during cold storage at 4-11°C (Arnal and Del R ıo, 2004;Orihuel-Iranzo et al, 2010), nevertheless at 0-1°C the drastic firmness loss only occurs when fruit are transferred to shelf life temperatures (Arnal and Del R ıo, 2004;Salvador et al, 2004). Therefore the use of treatments to control CI becomes necessary to cold storage persimmon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main CI symptom of this cultivar is a fast firmness loss. This flesh softening can be exhibited during cold storage at 4-11°C (Arnal and Del R ıo, 2004;Orihuel-Iranzo et al, 2010), nevertheless at 0-1°C the drastic firmness loss only occurs when fruit are transferred to shelf life temperatures (Arnal and Del R ıo, 2004;Salvador et al, 2004). Therefore the use of treatments to control CI becomes necessary to cold storage persimmon.…”
mentioning
confidence: 99%
“…In 'Rojo Brillante' persimmon, microstructural studies have shown that 1-MCP preserves the integrity of cell walls and adhesion between adjacent cells (P erez-Munuera et al, 2009). Moreover, the loss of the cell walls integrity and the flesh breakdown associated with CI development has been linked to increased levels of ethylene (De Souza et al, 2011;Luo and Xi, 2005;Orihuel-Iranzo et al, 2010;Woolf et al, 1997). According to Orihuel-Iranzo et al (2010), the increase in ethylene production upon transfer from chilling to nonchilling temperature is part of the fruit chilling response since it does not occur at nonchilling temperatures, and it also appears to be responsible for the collapse of the fruit.…”
mentioning
confidence: 99%
“…3). For cold storage of between 30 and 60 days, ST content slight decreased to values of around 0.4%, which then remained constant in all the treatments, except in the control fruit, in which ST declined to around 0.3% after 90 d. Orihuel et al (2010) reported that during ULO cold storage, the soluble tannins of 'Rojo Brillante' fruits declined from 0.7 to 0.4% within 24 d. It must be noted that for 'Rojo Brillante' persimmons, the usual values for non-astringent fruit are 0.03-0.04% of ST. An ST concentration higher than 0.04%, and even one as low as 0.06%, may cause astringency . In fact, the sensory evaluation of the fruit in the present study revealed that 'Rojo Brillante' fruits remained highly astringent (astringency value = 4) throughout cold storage.…”
Section: Soluble Tannins and Sensory Evaluation Of Astringencymentioning
confidence: 82%
“…In 'Rojo Brillante' persimmon, microstructural studies have shown that 1-MCP preserves the integrity of cell walls and adhesion between adjacent cells . Moreover the loss of the cell walls integrity and the flesh breakdown associated with CI development has been linked to increased levels of ethylene (De Souza et al, 2011;Luo and Xi, 2005;Orihuel-Iranzo et al, 2010;. According to Orihuel-Iranzo et al (2010), the increase in ethylene production upon transfer from chilling to nonchilling temperature is part of the fruit chilling response since it does not occur at nonchilling temperatures, and it also appears to be responsible for the collapse of the fruit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation